Successful campus outreach for academic libraries building community through collaboration - Keeran, Peggy, 1959-; Forbes, Carrie, 1975- (Rowman & Littlefield, 2018)
"Successful Campus Outreach for Academic Libraries: Building Community Through Collaboration brings together a variety of ways academic libraries engage with communities. This edited volume is a resource for discovering new programming ideas and principles of effective marketing, and it will aid strategic thinking about outreach activities"--